Achievement of Higher Secondary School Students in Biology in Relation to their Conjunctive Concepts, Scientific Attitudes and Self-efficacy - Yadav, Manoj Kumar; Singh, Vinod Kumar (JOURNAL OF INDIAN EDUCATION, 2021)
The present study aimed to investigate the achievement of Class XI students in Biology in relation to the independent variables, i.e., Conjunctive Concepts, Scientific Attitudes and Self-efficacy. A sample of 300 students, studying in Class XI was pulled out from six higher secondary schools of Varanasi city affiliated to CBSE Board under the administration of either CBSE Board or Banaras Hindu University. Total of four tools were used for data collection; of which three were constructed and standardised by the researcher himself and one was a readymade tool. The constructed tools were— (i) Achievement Test in Biology (ATB) (ii) Conjunctive Concept Test in Biology (CCTB) (iii) A Students’ Self-Efficacy Scale in Biology (SSESB). The readymade tool was Action Affection Thinking Style Questionnaire (AATSQ) (Singh, 1988). Statistical analysis was made by calculating mean, standard deviation and regression analysis. The findings of the study indicate that only conjunctive concepts as an independent variable play a significant role in the achievement of higher secondary school students in Biology at formal operational stage. The other independent variables like Scientific Attitudes and Self-efficacy seem to be less effective for predicting the achievement scores in Biology.